2022
DOI: 10.32322/jhsm.1090756
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination rates and the causes of vaccine hesitancy among patients with end stage renal disease

Abstract: Aim: Chronic kidney disease creates a tendency to infections, and infections are the second most common reason for mortality following cardiovascular events in chronic kidney disease. Health authorities recommend vaccination against hepatitis B, annual influenza, pneumonia, zoster, tetanus, and new coronavirus disease for people with end-stage kidney disease. Vaccine-preventable diseases cause mortality in the adult population with chronic diseases. The primary purpose of this study is to investigate vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a study conducted by cancer patients in Turkey in March–November 2020, it was found that 102 (63%) of 162 cancer patients were not vaccinated against pneumococcus, although it was recommended [ 14 ]. Another recent study from our centre demonstrated that vaccination rates among end-stage renal failure patients against pneumonia and influenza were 36% and 55.8%, respectively [ 15 ]. In a study from Italy, it was shown that 15,011 participants who were 65 or older (53.4%) had received influenza vaccination during the 2019, and 3461 (12.3%) had received anti-pneumococcal vaccination [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by cancer patients in Turkey in March–November 2020, it was found that 102 (63%) of 162 cancer patients were not vaccinated against pneumococcus, although it was recommended [ 14 ]. Another recent study from our centre demonstrated that vaccination rates among end-stage renal failure patients against pneumonia and influenza were 36% and 55.8%, respectively [ 15 ]. In a study from Italy, it was shown that 15,011 participants who were 65 or older (53.4%) had received influenza vaccination during the 2019, and 3461 (12.3%) had received anti-pneumococcal vaccination [ 16 ].…”
Section: Discussionmentioning
confidence: 99%